Corrigendum - Agrivita Agrivita (AGRIVITA, Journal of Agricultural Science, 2022)
Corrigendum to “Synergistic Action of PGPR and Biofungicide with Active Ingredient of Cladosporium clasporioides to Control White Rust on Chrysanthemum” [AGRIVITA Journal of Agricultural Science, 44(1), 31-39]